Pancasila Sebagai Kisah - Donny Danardono (JURNAL HUKUM, POLITIK DAN KEKUASAAN, 2021)
Pancasila cannot be an ideology. Because an ideology―as an absolute truth―will deny other ideologies. So to believe in Pancasila as an ideology is to believe that one day Pancasila will be eliminated by other ideologies. However, the impossibility of Pancasila becoming an ideology will not diminish its nobility. After all, Pancasila―which was raised in the debate on the basis of an independent Indonesian state between Islamic and nationalist groups―is a historical text. It will not be erased from the history of the Indonesian nation-state. Pancasila―which emerged from the debate at BPUPKI―is a story about how individuals in a pluralistic society want to live as a nation in the same country.